Pengembangan Media Kincir Angin Model Vertikal Axis Pada Pembelajaran Arus Listrik Bolak-Balik - Dodi Dinata; Hadma Yuliani; Jhelang Annovasho (Universitas Hamzanwadi, 2024)
This research was motivated by students' low understanding of alternating current concepts, with 68% of students experiencing difficulties and an average daily test score of only 65, below the minimum completion criteria of 75. The study aimed to develop and test the validity of a vertical axis windmill learning media in enhancing students' understanding of alternating current concepts at MA Darul Ulum Palangka Raya. The Research and Development (R&D) method with a 4D model (Define, Design, Develop, Disseminate) was used in media development, with validation conducted by media experts using assessment instruments for appearance and attractiveness aspects. Data analysis employed percentage techniques to determine media feasibility levels. Results showed satisfactory validity levels, with appearance aspects reaching 87.5% (highly valid) and attractiveness aspects at 75.0% (valid). This learning media proved suitable for physics education, featuring the ability to demonstrate alternating current generation principles practically and interactively through a vertical axis windmill system equipped with mini generators and digital oscilloscopes.